2015
DOI: 10.1038/sc.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

3D angioarchitecture changes after spinal cord injury in rats using synchrotron radiation phase-contrast tomography

Abstract: Study design: A basic experiment study. Objectives: An understanding of the three-dimensional (3D) angioarchitecture changes that occur after SCI will improve our knowledge of the pathogenesis of SCI and aid in the development of valuable therapeutic strategies to improve its poor outcomes. Our aim was to visualize the normal and traumatized spinal angioarchitecture in 3D using a high-resolution synchrotron radiation phase-contrast tomography (SR-PCT) and evaluate its diagnostic capability. Setting: SCI Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Among all these imaging methods, PPCI is the simplest to implement, requiring only a double-crystal monochromator without the need for additional complex optical components 21 22 . PPCI can provide excellent phase contrast information about soft tissue, such as the liver, brain and spinal cord vessels, and cartilage, especially in the human knee joints 23 24 25 26 27 28 29 . The 3D morphology of small objects, even individual cells, can be obtained with high spatial and contrast resolution using this method 30 .…”
mentioning
confidence: 99%
“…Among all these imaging methods, PPCI is the simplest to implement, requiring only a double-crystal monochromator without the need for additional complex optical components 21 22 . PPCI can provide excellent phase contrast information about soft tissue, such as the liver, brain and spinal cord vessels, and cartilage, especially in the human knee joints 23 24 25 26 27 28 29 . The 3D morphology of small objects, even individual cells, can be obtained with high spatial and contrast resolution using this method 30 .…”
mentioning
confidence: 99%
“…In addition to inhibiting astrogliosis, it has been reported that hypothermia can promote the expression of pro-angiogenic factors. Vascular disruption is a common traumatic event after SCI, resulting in hemorrhage, a reduction in spinal cord blood flow and ischemia [ 106 , 107 , 108 ]. Accordingly, inducing angiogenesis is a therapeutic strategy to promote spinal cord repair.…”
Section: Mechanisms Of Hypothermia-mediated Protectionmentioning
confidence: 99%
“…Within SRμCT studies, the number of collected projections reported can vary widely. Various nervous system studies have collected 720 20 , 21 , 501–2000 22 , 1600 2 , 1800–2400 23 and 2000–2400 3 projections. The minimal number of projections that should be collected to avoid undersampling at the edge of the field of view is calculated by multiplying the pixel width of an imaging system (perpendicular to the rotation axis) by π/2 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Inline phase contrast is a simple phase imaging method in which contrast is increased by increasing the propagation distance (PD) between sample and detector (or scintillator, for a scintillator-coupled camera). It is unclear whether phase contrast can augment tissue stain contrast, but inline phase contrast of unstained samples has enabled visualisation of murine spinal vasculature 20 , large-diameter motoneurons 22 , 29 , cerebral vasculature 5 and individual Purkinje cells in human post-mortem cortical tissue 3 . Details of how phase contrast was optimised have not commonly been reported, with PDs for nervous system samples varying from 300 mm 20 to 500 mm 5 and even 2,300 mm 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation